2018
DOI: 10.1002/jocc.12107
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary College Student Anxiety: The Role of Academic Distress, Financial Stress, and Support

Abstract: Mental health concerns, especially anxiety, are increasingly prevalent among college students. The authors analyzed data from the Center for Collegiate Mental Health 2013–2014 database to provide insight about student anxiety as reported by students and their counselors. Analyses showed that academic distress accounted for the largest amount of variance in anxiety, followed by financial stress, family support, and peer support. Sociodemographic variables had small effects, indicating a universality of anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(74 citation statements)
references
References 42 publications
4
56
0
1
Order By: Relevance
“…Students who have financial support exhibited lower anxiety prevalence than students who did not receive any financial support. This is consistent with a study reported by Jones et al (2018). In their paper, Jones et al mentioned that financial support would affect not only mental health but also has an impact on the academic performance of the students.…”
Section: Academic Characteristicssupporting
confidence: 89%
“…Students who have financial support exhibited lower anxiety prevalence than students who did not receive any financial support. This is consistent with a study reported by Jones et al (2018). In their paper, Jones et al mentioned that financial support would affect not only mental health but also has an impact on the academic performance of the students.…”
Section: Academic Characteristicssupporting
confidence: 89%
“…The increasing prevalence of mental health concerns, particularly anxiety, among students in higher education, including graduate students, is noteworthy (Burton & Baxter, 2019;Jones et al, 2018). Concern about academic performance appears to be the greatest source of stress for college students (Jones et al, 2018). We have observed similar trends among our students in recent years, with stress and anxiety significantly impacting students' overall well-being and performance both in the academic setting and during fieldwork.…”
supporting
confidence: 55%
“…The increasing prevalence of mental health concerns, particularly anxiety, among students in higher education, including graduate students, is noteworthy (Burton & Baxter, 2019;Jones et al, 2018). Concern about academic performance appears to be the greatest source of stress for college students (Jones et al, 2018).…”
mentioning
confidence: 99%
“…While, moderate level of anxiety is important in student's life as it help to strive their goals [21]. Academic stress, financial, peer and family support are counted of the variance of collegiate anxiety [22]. Hence, teachers can help students in their difficulties to lessen anxiety [23].…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The highest weighted mean is 3.37 indicator5 and 7 which is analyzed as "a fair amount of hearing the announcement of a coming test and reading the first question on a final exam." There should be a program implemented regarding anxiety and stress management to help students [22]. The second highest is indicator is 4 with a weighted mean of 3.27 that interpreted as "a fair amount of turning the complete test paper."…”
Section: Presentation Analysis and Interpretation Of Datamentioning
confidence: 99%